Symposium: Human Resources and Information Technology. (Journal of Labor Research)
A special section on human resources (HR) and information technology (IT). Topics discussed include an introduction to HR and IT in terms of human resource management; the impact of e-HR on the human resource management function; HR information systems; the effects of IT on recruitment; managing appraisal in an information age; and IT and employment law.